PRESENT-DAY AUDIT TECHNIQUE. - Andreae, Roy (The Accounting Review, 1947)
Abstract In approaching the subject of audit technique, the matters which will be discussed will be confined to those applicable to an examination of financial statements wherein the public accountant's responsibility is limited to expressing his opinion of a balance sheet and income statement to be used for purposes of general publication, as distinct from the more detailed examination incidental to the verification of recorded receipts and disbursements or other individual transactions for the purpose of establishing their propriety and authenticity. A realistic concept of audit technique is generally acquired through basic scholastic training in the technical procedures of conducting an audit, careful study, and intensive research, supplemented by intelligent application of academic training to the situations encountered when this knowledge is put to the test in actual business practice. However, the technical knowledge obtained by study and actual experience will lack full effectiveness unless coupled with the indispensable exercise of imagination, alertness, vision and common sense.